2023
DOI: 10.1108/rpj-03-2022-0087
|View full text |Cite
|
Sign up to set email alerts
|

Influence of processing parameters tuning and rheological characterization on improvement of mechanical properties and fabrication accuracy of 3D printed models

Abstract: Purpose Fabrication settings such as printing speed and nozzle temperature in fused deposition modeling undeniably influence the quality and strength of fabricated parts. As available market filaments do not contain any exact information report for printing settings, manufacturers are incapable of achieving desirable predefined print accuracy and mechanical properties for the final parts. The purpose of this study is to determine the importance of selecting suitable print parameters by understanding the intrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…These materials have a structure consisting of a matrix, which can be solid or flexible, and voids called pores. These porous structures can have different sizes, shapes, and arrangements, giving them different properties and applications [44]. The matrix, which is the solid part of the structure, surrounds and holds the pores.…”
Section: Better/worse Heat Transfer Due To Complex Geometries and Int...mentioning
confidence: 99%
“…These materials have a structure consisting of a matrix, which can be solid or flexible, and voids called pores. These porous structures can have different sizes, shapes, and arrangements, giving them different properties and applications [44]. The matrix, which is the solid part of the structure, surrounds and holds the pores.…”
Section: Better/worse Heat Transfer Due To Complex Geometries and Int...mentioning
confidence: 99%
“…Apart from the usual factors such as stacking sequence, fiber volume, and fiber orientation, the mechanical performance of printed parts was influenced by printing speed, nozzle diameter, and temperature, build orientation, and layer thickness. [29][30][31][32][33] In the present review, the authors revealed the recent developments in the AM technique, especially the sheet lamination method and FDM. Moreover, process parameters for obtaining the optimized performance of the manufactured 3-D printed products have been discussed.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to alter process parameters becomes useful when manufacturing printed components for structural applications. Apart from the usual factors such as stacking sequence, fiber volume, and fiber orientation, the mechanical performance of printed parts was influenced by printing speed, nozzle diameter, and temperature, build orientation, and layer thickness 29–33 …”
Section: Introductionmentioning
confidence: 99%
“…The current issue and full text archive of this journal is available on Emerald Insight at: https://www.emerald.com/insight/1355-2546.htm developed as secondary processes to ameliorate the surface integrity and dimensional accuracy of the printed parts (Hashmi et al, 2023a;Tiwary et al, 2022a). The preprocessing techniques are divided into the optimization of printing machine structure (Chu et al, 2021;Marion et al, 2023;Xu et al, 2022) and feedstock filament (Dontsov et al, 2020;Ginoux et al, 2023;Yan et al, 2023), printing strategy optimization (Afsharkohan et al, 2023;Côt e et al, 2023;Jiang et al, 2022;Wang et al, 2021) including printing path, printing speed, build orientation and layer thicknessand slicing optimization methods (Mosleh et al, 2023;Nayyeri et al, 2022;Vinoth Babu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%